UJI SIFAT FISIKA DAN KIMIA MADU HUTAN (Apis dorsata) BERDASARKAN SNI 8664-2018 - Azmalaeni Rifkah Ansyarif (Cokroaminoto Journal of Chemical Science, 2023)
Forest honey (Apis dorsata) is a liquid produced by honey bees and has a sweet taste. The quality of forest honey is determined based on SNI 8664-2018. The purpose of this study was to determine the quality of forest honey from the Berau area, East Kalimantan in terms of physical and chemical properties of honey based on SNI. Some of the honey qualities tested in this study are water content, ash content, HMF, acidity, and reducing sugar. The results obtained were the moisture content of honey showed a result of 20.19 %b/b, ash content showed 0.45 %b/b, HMF showed 28.91 mg/kg, acidity in honey showed 43.47 milliekivalen/kg, and reducing sugar showed a result of 68.21 %b/b. The results obtained show that the quality of the honey samples studied is in accordance with the Indonesian National Standard (SNI) 8664-2018.